Staatsverschuldung, Banken und Demokratie: Die Bedeutung von Sinnverbund und der Einheit von Handeln und Haften in der Schuldenkrise der EWU - Heike Walterscheid (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2014)
– Members of the European Currency Union and even a majority of all other Member States of the European Union are faced with high public and private depts. It is almost obvious that many Member States will have a problem with repaying depts and even are endanger to fall through interest payment. Thus, citizens within the territories of the European Currency Union are faced with an unpredictable risk of liability in case of bank failure and/or bankrupted states. Given that exit is almost no individual option yet, this implies the risk of a compulsory infringement into private assets of European citizens. Thus, losses caused by governments and banks, which both genuinely origin from political failure, will be socialized. Since European democracies are not aware of the implication of fractionized acting rights, which per se should build an internalizing unit of acting rights and therefore unify acting and liability, they are faced with serious complications into outmaneuver now- assuming that they really want to.
Keywords: 330; Property Rights; Rules; Regulation; Political Competition; Lobbyism; Fiscal Depts; Money Policy; European Central Bank; Banking System; European Currency Union; European Union; Sovereignty; Liability; Structural Couplings; Sense Interconnection; Public Choice; Fractionation; Democracy; Social System Theory; Evolution; Externalities; Internalization